Computer-based Interactive Learning Photographic Images in Veterinary Pathology. - Sutton, R. H. (Australian Learning and Teaching Council (ALTC), 1995)
This is a final report for a 1995 National Teaching Development Grant funded by the Committee for the Advancement of University Teaching. The report summarises the project, details its major objectives and achievements, and describes the teaching development.